Arsenic and Antimony in Hydrothermal Plumes from the Eastern Manus Basin, Papua New Guinea. (15th April 2018) - Zeng, Zhigang; Wang, Xiaoyuan; Qi, Haiyan; Zhu, Bowen
Abstract : Studies on the concentrations of arsenic (As) and antimony (Sb) in seawater columns are very important for tracing hydrothermal plumes and understanding fluid characteristics of seafloor hydrothermal systems. The total As, Sb, Mn, and Cl − concentrations of three hydrothermal plume seawater column samples have been studied at Stations 18G, 18K, and 18B in the eastern Manus back-arc basin, Bismarck Sea, Papua New Guinea. At Stations 18G and 18K, the plumes above North Su and near the Suzette site in the SuSu Knolls hydrothermal field are both enriched in As, Sb, and Mn and depleted in Cl, as a result of contribution of As-Sb-Mn-enriched and Cl-depleted vent fluid outputs to the hydrothermal plume, which is most likely generated in the subseafloor by fluid-rock interaction, magma degassing, or phase separation (boiling of hydrothermal fluid). The plume at Station 18B is enriched in As, Sb, Mn, and Cl, suggesting that As-Sb-Mn-Cl-enriched fluid discharges from vents, which have been generated by fluid-rock interaction. The concentrations of As and Sb anomalous layers, like manganese (Mn), are higher than those of the other layers in the three hydrothermal plume seawater columns. As and Sb with Mn showed a positive correlation (R 2 > 0.8, p < 0.05 ), and the distributions of As and Sb within the hydrothermal plume are not controlled by particle adsorption or biogeochemical cycles, suggesting that As and Sb, like Mn, can be used to detect and describe the characteristics of hydrothermal plumes in seawater environment. In addition, anomalous layer with As/Sb ratio lower than those of ambient seawater at the same temperature is found in the eastern Manus basin, suggesting that the As/Sb ratio may also act as an effective tracer reflecting the effect of hydrothermal activity on As and Sb in the seawater column.